The effects of maternal diet and breastfeeding on children with asthma and allergy - A. Revelas; T. Katasos (South African Family Practice)
The increase in the prevalence of asthma and allergic diseases highlights the need for devising effective prevention strategies. Several studies have investigated the preventive effect of maternal avoidance of highly allergenic foods, such as cow’s milk, eggs, and nuts, during pregnancy to protect the foetus from the effect of food allergens ingested by the mother.